2021
DOI: 10.1016/j.pmedr.2021.101546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neighborhood resources and mental health in American military Veterans using geographic information systems

Abstract: Highlights Four meaningful neighborhood resource groups were identified by clustering. Living in alcohol-permissive/tobacco-restrictive neighborhoods had negative impacts. Place of residence and distance to the closest VA care facility were not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Studies have found a strong correlation between area deprivation and poor mental health outcomes, such as depression and anxiety. 14,31 Factors that contribute to this correlation include limited access to mental health services, social isolation, financial stress, and exposure to violence and crime. Living in an area with a high ADI can also lead to increased levels of chronic stress, which can negatively affect mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found a strong correlation between area deprivation and poor mental health outcomes, such as depression and anxiety. 14,31 Factors that contribute to this correlation include limited access to mental health services, social isolation, financial stress, and exposure to violence and crime. Living in an area with a high ADI can also lead to increased levels of chronic stress, which can negatively affect mental health.…”
Section: Discussionmentioning
confidence: 99%
“…At the broader environmental level, resilience training and mental health screenings with access to mental health treatment provided by the military can also influence outcomes (Britt et al., 2013). Neighbourhood‐level social determinants (e.g., living in alcohol‐permissive neighbourhood) are increasingly recognised as influencing mental health (Park et al., 2021) and may have important implications for the resilience of MSMs.…”
Section: Conceptualising Resilience In a Military Contextmentioning
confidence: 99%
“…Public health experts and policymakers use SV to identify neighborhoods requiring additional resources to reduce their risk of experiencing negative physical health outcomes . SVs have more recently been used to study community mental health (MH) and substance use disorders (SUDs) . Because SV is often context dependent, empirical research is needed to guide selection of SV indices to inform community-level interventions.…”
Section: Introductionmentioning
confidence: 99%
“…6 SVs have more recently been used to study community mental health (MH) and substance use disorders (SUDs). [7][8][9][10][11][12][13] Because SV is often context dependent, empirical research is needed to guide selection of SV indices to inform community-level interventions.…”
mentioning
confidence: 99%